Kecepatan Tumbuh Benih Kelapa Sawit (Elaeis guineensis Jacq.) pada Dua Tempat Pengambilan Tanah Rawa Lebak - Mahdiannoor; Nur Hafizah; Heru Setiawan (Rawa Sains: Jurnal Sains STIPER Amuntai, 2018)
Along with the increasing demand for palm oil has the world's population, it is necessary to think about efforts to increase the quality and quantity of palm oil production. One of the factors such as planting material in the form of seeds, it is necessary to act technical culture or good seed treatment. Oil palm seedlings can be done in two stages: initial seeding (prenursery) and moved at the age of 2.5-3 months when they fulfill the criteria nursery ready to move to the main (main nursery). This study aims to (i) determine the speed of growth of oil palm seeds and, (ii) obtain the best type of soil for growing speed of oil palm seeds in two places making swampy marshland. The research was conducted in the Pangkalan Sari Village, Sungai Pandan Sub-district, Hulu Sungai Utara Regency in July-August 2013, using a completely randomized design (CRD) with a single factor. Factors studied were two lebak wetland of origin of uptake (T) as much as two levels and repeated nine times. The results showed that the two treatments had no effect lebak wetlands on many shoots observation variables age 14 and 28 days after seeding(DAS), the amount of leafage of 14 DAS, seedling height 14 DAS, and significant observations on many variables shoots the age of 42 DAS, number of leaves age 28 and 42 DAS, and a very significant effect on seedling height observation variables age 28 and 42 DAS.